Vertical Head and Eye Movements During Baseball Batting. - Fogt, Nick; Persson, Tyler W. (Optometry & Visual Performance, 2020)
Background: The purpose of this paper is to describe a method used to measure vertical head and eye movements and gaze positions of baseball batters and to report the initial findings generated with this method. Method: Two former collegiate baseball players participated. Subjects batted balls from a pitching machine. Results: Responses were similar for the two subjects. The head demonstrated a small upward rotation, followed by a downward rotation. The eye was rotated opposite to the head throughout portions of the swing, while gaze was directed below the ball (more for one subject than the other) for much of the pitch trajectory. Discussion: These data align with previous assertions that in baseball batting, players attempt to keep pitched balls in a constant egocentric direction.